2008
DOI: 10.1038/onc.2008.446
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D1 repressor domain mediates proliferation and survival in prostate cancer

Abstract: Regulation of the androgen receptor (AR) is critical to prostate cancer (PCa) development; therefore, AR is the first line therapeutic target for disseminated tumors. Cell cycle dependent accumulation of cyclin D1 negatively modulates the transcriptional regulation of the AR through discrete, CDK4-independent mechanisms. The transcriptional co-repressor function of cyclin D1 resides within a defined motif termed ther repressor domain (RD), and it was hypothesized that this motif could be utilized as a platform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 73 publications
4
17
0
Order By: Relevance
“…The prostate is a unique model to study the transcriptional consequence of cyclin D1 because androgens are important for the growth and survival of PCa cells. The mechanisms by which cyclin D1 elicits transcriptional repression have been preliminarily characterized (23,30,32,34,36), and the clinical importance has been suggested because human PCa specimens that lack cyclin D1 are associated with elevated serum PSA (27). The current study was conducted using physiological concentrations of androgen, and the number of overall androgen-regulated transcripts identified is consistent with previous reports (78 -81).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The prostate is a unique model to study the transcriptional consequence of cyclin D1 because androgens are important for the growth and survival of PCa cells. The mechanisms by which cyclin D1 elicits transcriptional repression have been preliminarily characterized (23,30,32,34,36), and the clinical importance has been suggested because human PCa specimens that lack cyclin D1 are associated with elevated serum PSA (27). The current study was conducted using physiological concentrations of androgen, and the number of overall androgen-regulated transcripts identified is consistent with previous reports (78 -81).…”
Section: Discussionsupporting
confidence: 76%
“…Thus, the ability of cyclin D1 to suppress AR activity appears to be diminished in PCa, consistent with the role of AR in promoting tumor development and progression (35). Conversely, introduction of the isolated cyclin D1 domain (repressor domain) responsible for transcriptional regulation of AR revealed that this functional motif is sufficient to attenuate ligand-dependent AR activity, cooperate with AR-directed therapeutics, and reduce cell viability in AR-dependent PCa cells (36). Combined, these findings identify cyclin D1 as a major effector of AR function and cellular outcomes in PCa.…”
mentioning
confidence: 86%
“…However, the central domain (142-253 aa), which is necessary for interactions with transcription factors or nuclear receptors (34)(35)(36), is required for this activity. Cyclin D1 is located at the OMM, where it binds VDAC through its central domain.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the Rb protein family, cyclin D-CDK4 complex was found to phosphorylate other transcription factors involved in cell proliferation/arrest, such as the transcription factor SMAD3 and the myb like transcription factor, DMP1 (3,4). Moreover, Cyclin Ds have been shown to interact with transcription coactivators/corepressors such as CBP, p300, P/CAF and HDACs (5)(6)(7)(8) and a repressor domain distinct from the CDK regulatory domain has been identified on CycD1 (9). As such, Cyclin Ds play important roles as CDKdependent and -independent transcriptional modulators.…”
mentioning
confidence: 99%